2004
DOI: 10.1055/s-2004-832649
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Baicalin in Rats and its Interactions with Cyclosporin A, Quinidine and SKF-525A: A Microdialysis Study

Abstract: Baicalin, a flavone glucuronide derived mainly from the root of Scutellaria baicalensis, has been used in traditional Chinese medicine as an anti-inflammatory and anti-viral agent. To explore whether the disposition of baicalin is related to multidrug resistance P-glycoprotein (P-gp), baicalin (3, 10 and 30 mg kg(-1); i. v.) was injected to rats for a pharmacokinetic study using microdialysis coupled with HPLC. The results indicate that baicalin goes through hepatobiliary excretion against a concentration grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…(28) The nonlinear pharmacokinetics might be because absorption of the PUE has an inhibitory effect on the concentration. (29) It was previously reported that the AUC of BAL in rats did not show any dose-related increase in the range of 3 to 30 mg/kg, (30) and the AUC of BAL in GQD decreased in the Scutellariae Radix Decoction in dogs. (27) In this article, the AUC 0-48h of BAL showed a good dose-related increase of PUE (r=0.993) in the range from 100 to 300 mg/kg, indicating that PUE dramatically affected the absorption of the BAL in mice.…”
Section: Discussionmentioning
confidence: 96%
“…(28) The nonlinear pharmacokinetics might be because absorption of the PUE has an inhibitory effect on the concentration. (29) It was previously reported that the AUC of BAL in rats did not show any dose-related increase in the range of 3 to 30 mg/kg, (30) and the AUC of BAL in GQD decreased in the Scutellariae Radix Decoction in dogs. (27) In this article, the AUC 0-48h of BAL showed a good dose-related increase of PUE (r=0.993) in the range from 100 to 300 mg/kg, indicating that PUE dramatically affected the absorption of the BAL in mice.…”
Section: Discussionmentioning
confidence: 96%
“…Tsai and Tsai (2004) reported that baicalin was not detected in the striatum after intravenous administration (30 mg/kg) alone or combined with cyclosporine or quinidine (each at 10 mg/kg) at a detection limit of 5 ng/mL. However, recently Zhang et al (2006) demonstrated that baicalin (90 mg/kg) could pass through the BBB and distribute to the cerebral nuclei in normal rats.…”
Section: Pharmacokineticsmentioning
confidence: 95%
“…In the recent years, strong effect on cancer and HIV of BC was found [4][5][6]. In spite of plenty of superiorities, the low water-solubility of BC brought many defects such as weak stability in solution, poor absorption and low bioavailability [2,7]. A series of BC-loaded formulations have been developed including gelling system [8], solid lipid nanoparticles [9], phospholipid complex [10], coprecipitate [11], nanoemulsion [12], and solid nanocrystals [13].…”
Section: Introductionmentioning
confidence: 99%